Excess pore water pressure and seepage in slopes induced by breaking internal solitary waves. (1st January 2023) - Tian, Zhuangcai; Jia, Lei; Xiang, Jiaming; Yuan, Guotao; Yang, Kun; Wei, Jun; Zhang, Mingwei; Shen, Honglei; Yue, Jianhua
Abstract: Internal solitary waves (ISWs) can induce the dynamic response of the seabed when they propagate over the seabed. In particular, the interaction between ISWs and the seabed is complex on slopes. In our study, the breaking of ISWs was simulated by Large Eddy Simulation (LES), and the pressure induced by ISWs was analyzed. In addition, the excess pore water pressure in the seabed was calculated based on Biot's consolidation theory. We found that the ISW-induced pressure changed the polarity when they propagated over the slope. The change rate of polarity increased with an increase in slope angle. However, the change of polarity was not obviously related to the breaking mechanisms of ISWs. Two distinct seepage fields existed in the whole seabed with sloping topography. In the flat region and near the foot of the slope, pore water flowed upward under the action of the ISW-induced negative pressure. The pore water near the top of the slope flowed downward because the ISW-induced pressure turned positive. Then, the two different parts of the seabed faced different failure risks. This study provides a basis for evaluating the seabed stability influenced by ISWs and contributes to researching the transformation of seabed topography induced by ISWs. Highlights: The ISW-induced pressure on the whole slope was studied and it changed polarity when ISWs propagate over slope. In the flat and near the foot of the slope, pore water flowed upward induced by negative ISW-induced pressure. The pore water nearing the top of slope flowed downward where the pressure induced by ISWs turned positive. ISW-induced pressure changed polarity had no obvious relation to the breaking mechanisms of ISWs.